The Problems of Translating Prepositions in Shakespearean Othello into Arabic - R. M. Qassim Agha; Sahar Mahfoodh Salih (PROSPECTIVE RESEARCHES, 2023)
This paper aims at shedding some light on prepositions in English as have been discussed by traditional structural and transformational generative grammarians. By examining the trends of thought adopted by each of the three schools and studying the features and uses of the English prepositions under investigation, one can find out that traditional grammarians have dealt with meaning as a basis for analysing and using not only prepositions, but all other parts of speech as well. That is to say, meaning, not form, is their only criterion of analysis. The work attempts to verify the following hypotheses: 1. The four translators of Othello variably employ Nida's (1964) models for translation. 2. Nil equivalence is likely to appear in Arabic texts. 3. Prepositions occur more frequently in English than they do in Arabic. With regard to the main findings, the translation of this type of text is a critical and difficult test for the competence of any translator to choose the most appropriate equivalence. As for the hypotheses they are valid.